Inventarisasi dan Identifikasi Lebah pada Tanaman Kacang Panjang (Vigna sinensis L.) di Kabupaten Ogan Ilir, Sumatera Selatan - Nugroho, Akmal; Mawarni, Aprilliyah; Sephiani, Erliza Rizki; Hariyanto, Muhamad Agus; Auda, Nilam Naslatul; Madya, Sakha Prawira; Umayah, Abu; Gunawan, Bambang; Arsi, Arsi (Seminar Nasional Lahan Suboptimal, 2022)
Nugroho A, Mawarni A, Sephiani ER, Hariyanto MA, Auda NN, Madya SP, Umayah A, Gunawan B, Arsi A. 2022. Inventory and identification of bees on long bean plants (Vigna sinensis L.) in Ogan Ilir Regency, South Sumatra. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang 27 Oktober 2022. pp. 614-620. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Most plants depend on mutualistic relationships between plants and pollinators, one of which is long beans (Vigna sinensis L.). Long beans (Vigna sinensis L.) are plantation crops that are widely exploited by farmers. The purpose of this study is to provide information on the Inventory and Identification of Bees on Long Bean Plants (Vigna sinensis L.) in Ogan Ilir Regency, South Sumatra. This observation uses descriptive exploratory methods, namely by conducting sampling activities, collecting data in the field, and identification. Observations were made on farmers land planted with peanuts (Vigna unguiculata). Data was collected by direct observation and sampling was done by purposive sampling using a plastic bag. The results of field observations showed that the bees in the long bean plantation in Tanjung Seteko Village, Timbangan Village, and Pulau Semambu Village were Apis cerana bees. The total number of Apis cerana species obtained from three villages was 75. In the village of Tanjung seteko, the Apis cerana species obtained were 34, in the sub-district the scales of Apis cerana species obtained were 17, and in Pulau Semambu village, the Apis cerana species obtained were 24. So, the species of bees that were observed in Tanjung Seteko Village, Timbangan Village and Pulau Semambu Village amounted to one species, namely Apis cerana. This research can be given to this research by knowing the identification of the bee, we can find out what its role is and the benefits of the bee itself.